Alternating group actions on spin 4-manifolds - Li, Hongxia; Liu, Ximin (Mathematica Scandinavica, 2008)
Let $X$ be a smooth, closed, connected spin 4-manifold with $b_1(X)=0$ and non-positive signature $σ(X)$. In this paper we use Seiberg-Witten theory to prove that if $X$ admits a spin alternating $A_5$ action, then $b_2^+(X)≥ |σ(X)|/8 +3$ under some non-degeneracy conditions.